2002
DOI: 10.1128/jb.184.1.335.2002
|View full text |Cite
|
Sign up to set email alerts
|

The Global Posttranscriptional Regulator RsmA Modulates Production of Virulence Determinants and N -Acylhomoserine Lactones in Pseudomonas aeruginosa

Abstract: 2A: "(pME3849)" and "(pME6001)" should be deleted from all three graphs. The data are for the plasmid-free PAO1 and PAZH13 strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
140
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(145 citation statements)
references
References 0 publications
1
140
0
4
Order By: Relevance
“…It regulates multiple unrelated pathways such as central carbon metabolism, motility and biofilm formation, virulence and pathogenesis, quorum sensing and oxidative stress response (Fig. 2), although some subtle differences exist depending on the bacterial species studied [44,52,58,59,62,[66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81]. Several homologues have been identified in other bacterial species [82].…”
Section: Post-translational Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…It regulates multiple unrelated pathways such as central carbon metabolism, motility and biofilm formation, virulence and pathogenesis, quorum sensing and oxidative stress response (Fig. 2), although some subtle differences exist depending on the bacterial species studied [44,52,58,59,62,[66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81]. Several homologues have been identified in other bacterial species [82].…”
Section: Post-translational Regulationmentioning
confidence: 99%
“…In several species including Vibrio sp. and Pseudomonas sp., CsrA negatively regulates the production of AHL, although the underlying molecular mechanism is still unknown [79,101]. In E. carotovora subsp.…”
Section: Csra Regulates Group Behaviourmentioning
confidence: 99%
“…Thus, the two QS systems of P. aeruginosa are hierarchically arranged with the las system being on top of the signalling cascade (Latifi et al, 1996). A number of regulators, including Vfr (Albus et al, 1997), GacA (Reimmann et al, 1997), RsaL (De Kievit et al, 1999), MvaT (Diggle et al, 2002), RsmA (Pessi et al, 2001), DksA (Jude et al, 2003), QscR (Chugani et al, 2001), and VqsR (Juhas et al, 2004), have been identified that are involved in modulating the QS circuitry. An additional signal molecule, the P. aeruginosa quinolone signal, adds a further level of complexity, as it provides a link between the las and rhl systems (Pesci et al, 1999) by modulating expression of rhlRI and lasRI (McKnight et al, 2000;Diggle et al, 2003).…”
Section: Burkholderia Cepacia Infections In Cfmentioning
confidence: 98%
“…In strains of P. aeruginosa, the conserved GacS/ GacA system directs the synthesis of two small RNAs, designated RsmY and RsmZ, which antagonize one CsrA homolog, named RsmA (Reimmann et al 1997;Pessi et al 2001;Heurlier et al 2004;Kay et al 2006) (Fig. 2b).…”
Section: Phenazines and Ahls As Signalsmentioning
confidence: 99%
“…2a). In P. aeruginosa, target genes include hcnA and the phz genes (Reimmann et al 1997;Pessi et al 2001) (Fig. 2b).…”
Section: Phenazines and Ahls As Signalsmentioning
confidence: 99%